ASOSIASI TALI KUPU-KUPU (Bauhinia acuminata Blume.) DENGAN POHON INANG PADA PLOT MONITORING TAMAN WISATA ALAM GUNUNG MEJA MANOKWARI - SIMSON L MANDABAYA; NOVITA PANAMBE; MELIZA S. WORABAI; NOVIKA RUKKA (Fakultas Kehutanan UNIPA, 2020)
Gunung Meja Nature tourist Park is one of the low land tropical forest ecosystems in Manokwari which had various potention of its flora and fauna. The flora potention had relation or complex population, one of them is association between tali kupu-kupu (Bauhinia acuminata Blume.) with its host tree. The purpose of the study was to describe the asociation of B. acuminata with its host tree and its habitat at the low land at Gunung Meja Nature Tourist Park. The method used description with survey technique. The resluts showed that the total population of the trees associating with B. acuminate. There were 10 species i.e. Pometia coreacea, Pometia pinnata, Alstonia scholaris, Artocarpus incissus, Pimelodendron amboinicum, Pterocymbium beccarii, Antiaris toxicaria, Streblus elongate, Medusanthera laxiflora, and Pterygota horsfieldii which dominated by Pometia pinnata 11 trees. The association relation level of B. acuminata with the host tree P. pinnata was very close (2.506 %) while association relation level of B. acuminata was quite close with the host tree of A. scholaris (0.911 %), P. amboinicum (0.911 %), and the association level B. acuminata was not close with the host tree P. coreacea (0.683 %), P. beccarii (0.228 %), A. toxicaria (0.228 %), A. incisus (0.683 %), P. horsfieldii (0.683 %), S. elongata (0.456 %), and M. laxiflora (0.456 %).